Characterization of physical & mechanical properties of asphalt concrete containing low- & high-density polyethylene waste as aggregates. (27th September 2021) - Ullah, Safeer; Raheel, Muhammad; Khan, Rawid; Tariq Khan, Muhammad
Highlights: Low- & High-Density Polyethylene plastic waste can act as substitute for natural aggregates in asphalt. Synthetic plastic aggregates resulted in reduction of asphalt. Synthetic plastic aggregates enhance the resistance to rut development in asphalt. Synthetic plastic aggregates improve the resilient modulus of asphalt. Abstract: Coarse aggregate is one of the main ingredients of asphalt concrete as it plays a vital role in the serviceability and durability of a flexible pavement. This study aimed at evaluating the effect of partially adding waste plastic aggregates in asphalt mix and studying its influence on different physical and mechanical properties. For this purpose, plastic waste was collected from landfill sites and classified into low density polyethylene (LDPE) and high-density polyethylene (HDPE), and, shredded into aggregates of desired size. Natural aggregates were replaced with these synthetic aggregates in different proportions such as 5%, 15% and 25%. Results showed that the incorporation of both types of plastic wastes reduced the density of asphalt mixture due to increase in air voids. The stability and flow values increased up to 15% partial replacement of natural aggregates with LDPE and HDPE. Similarly, LDPE-25 samples had lowest rut depth followed by HDPE-25. HDPE-15 sample showed the highest value of resilient modulus with a percentage increase of about 168.5% as compared to control sample. The dynamic modulus of asphalt also improved with plastic aggregates. However, the dynamic modulus values reduced with the increase in frequency for all study samples.